Ab interno gel implant in patients with primary open angle glaucoma and pseudoexfoliation glaucoma - Hengerer, Fritz; Auffarth, Gerd U.; Yildirim, Timur Mert; Conrad-Hengerer, Ina (BMC ophthalmology, 2018)
To compare efficacy and safety results of an ab interno gel implant in patients with pseudoexfoliation glaucoma (PXG) and primary open angle glaucoma (POAG).
Gesehen am 08.01.2019